Soft computing techniques for machining of composites - Gaitonde, V. N.; Karnik, S. R.; Davim, J. Paulo (Materials science forum, 2013)
Even though composites are manufactured to near net shaped, machining has to be performed during the final production stage to get the finished products. Soft computing is a collection of methodologies that aim to exploit tolerance for imprecision, uncertainty and partial truth to achieve tractability, robustness and low solution cost. This special volume intends to draw a picture of the recent advances made in the soft computing assisted machinability studies for composite materials and includes the submission of high quality research articles. Suitable topics include the application to the m.